The art of Mantua : power and patronage in the Renaissance - Furlotti, Barbara (J. Paul Getty Museum, 2008)
Ch. 1. The city from Its origins to the medieval period -- Ch. 2. From the International Gothic to humanism : art and culture in the fifteenth century -- Ch. 3. Isabella d'Este and the culture of the studiolo -- Ch. 4. Giulio Romano at the court of Federico Gonzaga -- Ch. 5. Art and artists in the time of Cardinal Ercole and Duke Guglielmo Gonzaga -- Ch. 6. The creation of a myth : the patronage and collection of Duke Vincenzo Gonzaga -- Ch. 7. Ferdinando Gonzaga : an intellectual duke -- Ch. 8. Mantua from the crisis of 1627-30 to the end of the dynasty in 1708